Origami’s Enterprise 2.0 Solution: The Next Frontier in Computing? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
James Ong, founder and CEO of technology company, Origami Frontiers, exemplifies a new generation of western educated technocrats and market-savvy entrepreneurs. After nearly two decades in the US, Ong returned to his roots in 2002, fuelled by a vision to develop innovative enterprise solutions based on emerging Web 2.0 technologies. At a research seminar organised by the School of Information Systems, Singapore Management University, Ong described how he wanted to be a part of the technology revolution in Asia.